Epidemiological behavior of childhood obesity: A continental point of view (2024)
Weight excess during the childhood has been one of the most critical public health problems worldwide in the past few decades. It is considered a significant predictor of adulthood obesity, increased cardiometabolic diseases, and premature mortality. Since the Industrial Revolution, childhood obesity has risen due to sedentary lifestyles and poor eating habits, contributing to the development of obesogenic environments around children in different parts of the world. In this regard, Oceania is positioned as the continent with the highest prevalence globally; however, these results did not consider Australia and New Zealand’s data, probably due to the significant differences in population sizes. America has the second highest percentage of children under five who are overweight. Curiously, Asia’s obesity rates are more significant in higher socioeconomic statuses and urban areas than in children aged 2-4 years. Likewise, Africa displays similar epidemiologic behaviour. Qatar and Kuwait are the countries with the highest obesity prevalence on the continent. Moreover, Europe exhibits a notable South-North gradient, which establishes a higher prevalence of obesity in Mediterranean countries than the Nordic ones. In this regard, various prevention and interventional programs have been developed to combat this silent epidemic, focusing their efforts on nutritional education, improving children’s and parents’ lifestyles, and fighting the influence of the media on their behaviour, and decisions. Therefore, the objective of this review was to describe the epidemiological behaviour of childhood obesity from a continental perspective.